Evaluation of synergism between Cefotaxime and Allium sativum against Extended-spectrum beta-lactamase and Ambler class C co-producers - Pratibha J. Shah, Manita T. Williamson (Journal of Applied Pharmaceutical Science, 2019)
The present study evaluates the synergistic association between Cefotaxime and aqueous garlic (Allium sativum) extract (AGE) on extended spectrum beta-lactamase (ESBL) and Ambler Class C (AmpC) co-producing Escherichia coli strains from skin and soft tissue infections (SSTIs). Ceftazidime-resistant E. coli strains were screened for beta-lactamase production by phenotypic confirmatory disc diffusion test (PCDDT) and E-test. Antibacterial activity of AGE was examined by the disc diffusion method and the minimum inhibitory concentration (MIC) of Cefotaxime and AGE was determined. The synergistic association between Cefotaxime and AGE was evaluated by calculating the fractional inhibitory concentration (FIC) index, time-kill kinetics assay (TKA), and scanning electron microscopy (SEM). The zone of inhibition by AGE against the 27 E. coli co-producers of ESBL and AmpC ranged from 17 to 30 mm. The average MIC of Cefotaxime and AGE was found to be 570 μg/ml and 0.86% (4.28 mg/ml), respectively. The FIC index obtained by the checkerboard method established a synergistic association between Cefotaxime and AGE in 10 (37%) test strains, which was confirmed by TKA. The SEM analysis revealed complete cell degradation at 8 hours on the treatment with Cefotaxime-AGE combination. It can be stated that the AGE may aid Cefotaxime in the treatment of beta-lactamase producing E. coli strains from SSTIs.
Keywords: Beta-lactamase, Cefotaxime, aqueous garlic extract, synergy, time-kill kinetics assay, SEM.